The Influence of Transformational Leadership, Organizational Culture, Organizational Communication, and Organizational Commitment on Teacher Performance in Indonesia: A Study in Jambi Province - Mahesa Nababil; Robi Hendra; Akhmad Habibi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of transformational leadership, organizational culture, organizational communication, and organizational commitment on teacher performance in Keliling Danau District. In the context of education, teacher performance is influenced by various internal factors within the school organization. The research method used is descriptive quantitative with teachers and a sample of 325 teachers taken using the Slovin formula. Data were collected through a validated questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) techniques. The results of the study indicate that transformational leadership has a significant positive effect on teacher performance and organizational commitment. Organizational culture also contributes positively to organizational communication and teacher performance. Additionally, good organizational communication enhances teacher commitment, which in turn positively impacts their performance. These findings emphasize the importance of integrating leadership, culture, communication, and commitment in creating a productive work environment for teachers, particularly in areas with challenges such as Keliling Danau.